(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Disorders of endothelial function in CRAS are systemic in nature. In this regard, identifying violations of the adhesive properties of the vascular wall during the development of CRAS is of significant scientific and practical interest. Studying the content of soluble molecules of cell adhesion and migration of leukocytes in the blood serum of patients with CRAS will significantly expand the understanding of pathogenesis, diagnostic possibilities, and improve the prevention and treatment of this disease.